2020
DOI: 10.2967/jnumed.119.237180
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Radiosynthesis of 89Zr-DFO-Azepin-Onartuzumab for Imaging the Hepatocyte Growth Factor Receptor

Abstract: Methods that provide rapid access to radiolabeled antibodies are vital in the development of diagnostic and radiotherapeutic agents for positron emission tomography (PET) or radioimmunotherapy. The human hepatocyte growth factor receptor (c-MET) signaling pathway is dysregulated in a number of malignancies including gastric cancer, and is an important biomarker in drug discovery. Here, we used a photoradiochemical approach to produce 89Zr-radiolabeled onartuzumab (a monovalent, anti-human c-MET antibody), star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 33 publications
(21 reference statements)
2
44
0
1
Order By: Relevance
“…We recently demonstrated that metal ion binding chelates functionalised with a photoactivatable ArN 3 group can be used to prepare radiolabelled antibodies by either a two‐step conjugation and radiolabelling process or by a novel one‐pot approach . Simultaneous 89 Zr‐radiolabelling and light‐induced conjugation using a photoactivatable DFO‐ArN 3 derivative produced viable PET radiotracers (Scheme ) . Additionally, the photochemical conjugation process is compatible with standard formulation buffers, which allows direct synthesis of radiolabelled‐mAbs from approved drugs like Herceptin TM .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that metal ion binding chelates functionalised with a photoactivatable ArN 3 group can be used to prepare radiolabelled antibodies by either a two‐step conjugation and radiolabelling process or by a novel one‐pot approach . Simultaneous 89 Zr‐radiolabelling and light‐induced conjugation using a photoactivatable DFO‐ArN 3 derivative produced viable PET radiotracers (Scheme ) . Additionally, the photochemical conjugation process is compatible with standard formulation buffers, which allows direct synthesis of radiolabelled‐mAbs from approved drugs like Herceptin TM .…”
Section: Methodsmentioning
confidence: 99%
“…Formulated protein substrates included human serum albumin (HSA), the engineered antibody onartuzumab (formulated as MetMAb TM ), and the humanised IgG 1 immunoglobulin trastuzumab (formulated as Herceptin TM ). Simultaneous (one‐pot) photoradiolabelling reactions were performed in accordance with Scheme …”
Section: Methodsmentioning
confidence: 99%
“…In 2019, our group demonstrated that light-induced activation of chelates bearing aryl azide (ArN3) groups and radiolabelled with a variety of different radionuclides, including 68 Ga 3+ and 89 Zr 4+ ions, can produce viable PET radiotracers direct from formulated antibody solutions. [13][14][15][16][17][18][19][20] The underlying concept of bimolecular photochemically induced protein modification is shown in Figure 1. 19,21 The key motivation for developing an alternative protein conjugation and radiolabelling strategy was to eliminate steps that involved pre-purification of the protein and isolation of a functionalised (non-radiolabelled) intermediate molecule.…”
Section: Development and Overview Of The Protocolmentioning
confidence: 99%
“…[32] Our group has also explored the use of photoactivat-able chelates bearinga na ryl azide to make viable 68 Ga and 89 Zr PET radiotracersvia direct functionalisation of mAbs. [33][34][35][36] Here, we demonstrate that the photophysical properties of tetrazoles can be tuned through syntheticcontrol over the arylene substituents to facilitate the rapid and direct, bimolecular protein labellinga tw avelengths in the UVAr egion of the spectrum. Two-step photochemical conjugation and radiolabelling produced 89 Zr-labelled trastuzumab for PET imaging of human epidermal growth-factor receptor 2( HER2/neu)e xpression in tumours.…”
mentioning
confidence: 89%
“…used the photo‐induced cycloaddition process and labelled an alkene‐functionalised, tumour‐specific peptide with a modified tetrazole which allowed 68 Ga and 64 Cu radiolabelling for PET and optical imaging in a glioblastoma model [32] . Our group has also explored the use of photoactivatable chelates bearing an aryl azide to make viable 68 Ga and 89 Zr PET radiotracers via direct functionalisation of mAbs [33–36] …”
Section: Figurementioning
confidence: 99%